PERHATIAN ORANG TUA TERHADAP AKTIVITAS BELAJAR SISWA DI ERA PANDEMI COVID-19 - Hazzima Nengsih; Heru Purnomo (STKIP Persada Khatulistiwa Sintang, 2021)
The purpose of this article is to describe the role of parents' attention in caring for their children so that effective children's learning activities can be realized. The method used in this study is literature or what we are often familiar with as a literature study. Data analysis is that the sources of the reading are compiled, then analyzed, then the final result is compiled. The results of this study explain that the role of parental care needs to be studied, let alone be implemented by every parent wherever they are. This of course greatly affects children's learning activities, positive guidance, such as being given understanding, direction, advice that builds enthusiasm for learning so that children can correct the mistakes they make, allowing positive habits to be formed in a child, for example children can adjust themselves quickly, courageous and confident in making decisions. This is what we often hear with democratic guidance. On the other hand, if the parental education is not good and the parents' attention is very minimal, it will have a negative impact on children's learning activities, so that the child will feel lazy and not enthusiastic and not confident about their achievements.